Types of Interparental Conflict Associated with Child Triangulation: A Systematic Review - Fauzia Ramadhianty; Niken Hartati (Da'wa Faculty of Islamic State University Salatiga, 2026)
Interparental conflict frequently extends beyond the couple, escalating into a systemic dysfunction that directly involves the child, a clinical phenomenon known as triangulation. Despite widespread recognition of its harmful impact, the empirical understanding of which specific conflict types and underlying mechanisms actually draw children into these disputes remains fragmented. Consequently, this Systematic Literature Review (SLR) aims to synthesize how different characteristics of interparental conflict relate to variations in child triangulation, alongside the psychological and structural mechanisms that drive this shift. Following the PRISMA 2020 guidelines, we reviewed 20 primary empirical studies (published between 2015 and 2025) from Scopus, Web of Science, PubMed, and APA PsycINFO, evaluating their methodological quality using the Mixed Methods Appraisal Tool (MMAT). The narrative synthesis challenges the assumption of a simple, linear relationship between conflict severity and child involvement. Instead, triangulation is highly multidimensional and is most strongly triggered by child-related disputes, open hostility, covert tension, and coparenting breakdowns. The transition from a dyadic conflict to triangulation operates through a continuous feedback loop of individual factors (e.g., self-blaming attributions, threat appraisals, emotion dysregulation) and systemic vulnerabilities (e.g., blurred intergenerational boundaries and detouring). This complex interaction ultimately creates a deeply unhealthy but stable family adaptation termed